2021
DOI: 10.1038/s41598-021-85714-4
|View full text |Cite
|
Sign up to set email alerts
|

To drain or not to drain: the association between residual intraperitoneal gas and post-laparoscopic shoulder pain for laparoscopic cholecystectomy

Abstract: Residual intra-peritoneal gas may be associated with post-laparoscopic shoulder pain (PLSP), which is a frequently and disturbance compliant after surgery. Herein, we aimed to examine whether expiring residual gas via a surgical drain reduces the frequency and intensity of PLSP in the first day after laparoscopic cholecystectomy. 448 participants were enrolled in this prospective cohort study. The incidence and severity of PLSP after surgery were recorded. Of these, the cumulative incidence of PLSP in the drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…This suggests that minimizing residual gas at the end of surgery is beneficial for reducing postlaparoscopic shoulder pain. 27 Our study also revealed results consistent with studies.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that minimizing residual gas at the end of surgery is beneficial for reducing postlaparoscopic shoulder pain. 27 Our study also revealed results consistent with studies.…”
supporting
confidence: 92%
“…Therefore, a clear conclusion that postoperative drainage reduces pain following LC is not definitive. El-Labban et al26 also stated the necessity to use a drain 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, laparoscopic surgery can also induce postoperative shoulder pain, vascular injury, intestinal injury, urinary tract injury, air embolism, and other related complications. Among these complications, post‐laparoscopic shoulder pain is one of the most common complications of laparoscopic surgery, with an incidence rate of 34.1%–82.4% 1,2 …”
Section: Introductionmentioning
confidence: 99%
“…Medical practitioners have advised and used various techniques to minimize this, like preoperative administration of opioids or opioid-sparring analgesia, clonidine, preoperative pregabalin, wound site instillation of local anesthetics, and intraperitoneal irrigation with bupivacaine or ondansetron and suctioning of residual gas from the peritoneum before closure [3][4][5][6][7][8][9][10]. 1 2…”
Section: Introductionmentioning
confidence: 99%